Globalisation as a major factor modifying the patterns of tourism activity - Hołowiecka, Beata; Grzelak-Kostulska, Elżbieta (Bulletin of Geography. Socio-economic Series, 2013)
Globalisation is a complex and dynamic process that today influences many factors determining the development of tourism. It brings about economic, political, social and even cultural changes and drives the expansion of a single global market where the movement of capital, goods and people is much easier than it used to be. Globalization also has an intangible dimension – by enabling access to information and modern forms of communication and by stimulating the spatial mobility of populations it allows ideas to flow freely, as a result of which individuals learn new attitudes and behaviours. This article discusses the influence of globalization on the tourism preferences and tourism activity of Polish residents. The results of the earlier empirical research has confirmed that different social groups have their specific models of tourism activity, showing also which groups have responded to globalization the most strongly and the possible consequences this may have for tourism activity.